Hydrolysis Products Generated by Lipoprotein Lipase and Endothelial Lipase Differentially Impact THP‐1 Macrophage Cell Signalling Pathways. Issue 8 (22nd June 2013) - Essaji, Yasmin; Yang, Yanbo; Albert, Carolyn J.; Ford, David A.; Brown, Robert J.
Abstract: Macrophages express lipoprotein lipase (LPL) and endothelial lipase (EL) within atherosclerotic plaques; however, little is known about how lipoprotein hydrolysis products generated by these lipases might affect macrophage cell signalling pathways. We hypothesized that hydrolysis products affect macrophage cell signalling pathways associated with atherosclerosis. To test our hypothesis, we incubated differentiated THP‐1 macrophages with products from total lipoprotein hydrolysis by recombinant LPL or EL. Using antibody arrays, we found that the phosphorylation of six receptor tyrosine kinases and three signalling nodes—most associated with atherosclerotic processes—was increased by LPL derived hydrolysis products. EL derived hydrolysis products only increased the phosphorylation of tropomyosin‐related kinase A, which is also implicated in playing a role in atherosclerosis. Using electrospray ionization‐mass spectrometry, we identified the species of triacylglycerols and phosphatidylcholines that were hydrolyzed by LPL and EL, and we identified the fatty acids liberated by gas chromatography‐mass spectrometry. To determine if the total liberated fatty acids influenced signalling pathways, we incubated differentiated THP‐1 macrophages with a mixture of the fatty acids that matched the concentrations of liberated fatty acids from total lipoproteins by LPL, and we subjected cell lysates to antibody array analyses. The analyses showed that only the phosphorylation of Akt was significantly increased in response to fatty acid treatment. Overall, our study shows that macrophages display potentially pro‐atherogenic signalling responses following acute treatments with LPL and EL lipoprotein hydrolysis products.